Implementation of Inquiry-Based Learning (IBL) Through Ancient Tombs of Sultan Barumun Era to Enhance Historical Thinking Skills of MAN Barumun Students: A Qualitative Analysis - Burhanuddin, Burhanuddin; Nasution, Bincar (International Journal of Community Service (IJCS), 2026)
This qualitative research examines the implementation of Inquiry-Based Learning (IBL) through the ancient tombs and historical sites of the Sultan Barumun era to enhance historical thinking skills among students at Madrasah Aliyah Negeri (MAN) Barumun. Involving 50 students, 3 history teachers, 4 community guides, and 2 school administrators, the study employed mixed qualitative methods including structured observations (8 sessions), semi-structured interviews (7 participants), focus group discussions (2 sessions with 30 students), document analysis, student learning journals (weekly reflections), and site visits over a four-month period. Data were analyzed using thematic analysis with open and axial coding procedures to identify patterns in student engagement, understanding, and skill development. Results revealed significant improvements in students' historical thinking skills across six dimensions: source analysis and interpretation (7-student increase to Proficient level), historical contextualization (7-student increase), causation and chronological reasoning (16-student increase), evidence-based argumentation (Advanced category achievement), perspective recognition (38 students in Advanced category), and synthesis and conceptualization (1-student progression to Proficient level). Thematic analysis identified six primary themes: enhanced critical engagement (23 occurrences), deepened historical understanding (28 occurrences), active participation and agency (31 occurrences), emotional connection to heritage (26 occurrences), collaborative learning dynamics (29 occurrences), and implementation challenges (17 occurrences). The study demonstrates that IBL through culturally significant historical sites effectively develops students' capacity for historical thinking while fostering emotional connections to local Islamic heritage and regional identity..